PENERAPAN METODE DEMONSTRASI UNTUK MENINGKATKAN TEKNIK DASAR TENIS MEJA SISWA KELAS VI SDM 036 GOBAH KECAMATAN TAMBANG KABUPATEN KAMPAR - Rohima, Rohima (Aksara Public, 2017)
Research is motivated by the low capacity of the basic techniques of table tennis HR 036 students of class VI Gobah Mining District of Kampar. This study aims to determine the increase in the basic motion table tennis HR 036 students of class VI Gobah Mining District of Kampar district through the implementation of demonstration methods. This research was conducted in classes VI HR 036 Gobah Mining District of Kampar district. As the subjects in this study were students of class VI Class HR 036 Gobah Mining District of Kampar regency 2013-2014 school year the number of students as much as 31 people, including 20 male students and 12 female students. This research is a classroom action research (PTK) through the steps of planning, implementation, observation and reflection. Based on the results of research and discussion, we can conclude that the implementation of the activities Action Research (PTK) on HR 036 Gobah Conducting Action Research (PTK) on HR 036 Gobah Mining District of Kampar district can improve engineering capabilities sport of table tennis. Always an increase in each cycle of the table tennis technical skills through modified games in Class VI HR 036 Gobah Mining District of Kampar district, it is evident from the results of tests that have been carried out. Wherein from 37 the number of students, in initial tests obtained an average value categorized quite competent with the average value of 53.2, whereas in the first cycle engineering skill game of table tennis students rose to 67.7 by category competent enough, and the second cycle of average ability students also increased with the competent category with an average value of 87.1.